A New Genus, Luciargentis gen. nov. Revealed by Morphological and Phylogenetic Evidence in the Family Lecithoceridae from Tibet, China - Shuai Yu; Haotian Li; Shuxia Wang (Insects)
In this study, we describe a new genus, Luciargentis Yu and Wang, gen. nov. based on the new species, Luciargentis obesa Yu and Wang, sp. nov. Additionally, the genus is placed within the subfamily Crocanthinae, satisfying the criteria of Crocanthinae. We conducted a phylogenetic analysis of the family Lecithoceridae using a concatenated dataset that includes one mitochondrial marker (COI) and six nuclear markers (EF-1α, GAPDH, RpS5, CAD, wingless, and MDH), incorporating 17 exemplars from NCBI and 7 newly sequenced exemplars from this study. The yield tree topologies showed that Luciargentis obesa forms a strongly supported monophyletic group with Crocanthes prasinopis, a species of Crocanthinae. Moreover, Luciargentis + Crocanthes were found to be sister groups to Torodorinae. Images of the adults, wing venation, and genitalia of the new species are provided.